The Effectiveness of Counseling Using Quartet Card Media on Brushing Behavior in School-Age Children - Dewi, Ayu Ratna; A'yun, Quroti; Sutrisno, Sutrisno; Sulistyani, Herastuti (Jurnal Kesehatan Gigi, 2024)
Background: The community's low incidence of excellent and proper brushing behavior, which is primarily displayed by children (about 2%), is increasing the prevalence of dental decay. By employing the playing strategy, specifically with four card media, which has its own appeal due to the intriguing pictures, one can improve brushing behavior, which is now inadequate. Research Objective: To investigate the effectiveness of quartet card media counseling on toothbrushing behavior in elementary school students. This research used quasi experimental with pretest and posttest control group design. The samples were collected using total sampling, and they were 110 respondents. The sample is split into two groups: the experimental group and the control group. The data were collected using questionnaires for pretest and posttest. The data analysis used a Wilcoxon and Mann-Whitney test. Research Results: Tooth brushing behavior in elementary school students was 47.3% with good criteria, moderate 47.3%, and increased with good criteria 92.7%, while 7.3% following counseling. The experimental group's mean value was 14,36 compared to the control group's 12,64. The Wilcoxon test resulted in a p-value of 0.000, the Mann Whitney test obtained p=0.000. Conclusion: Counseling using quartet card media is effective in improving brushing behavior in elementary school children.Â Keyword : Effectiveness of counseling, quartet card media, brushing behavior.